Digitalization Global Reporting Format in International Juwata Airport Tarakan - Simbolon, Suse Lamtiar; Maulana Putra, Septian Tri Pradita; Jati Utama, Risqi Wahyu; Gaffari , Muhammad Zhabri (Politeknik Penerbangan Indonesia Curug, 2024)
The global reporting format at Juwata International Airport, Tarakan is still inefficient and uses too much paper. The purpose of this paper is to make global reporting format more efficient and not use a lot of paper / paperless. The method used to overcome the above problems is to digitize the global reporting format using the website US a platforms for data entry forms so that they are easier to fill out and efficient. The results of the website usage test shows that filling in the global reporting format data is efficient and paperless and the website can be used when online. Based on the results of the above method, it is concluded that digitizing reporting is very efficient and does not use a lot of paper, and can help in storing the recap of reporting results so that reporting data is note lost and neatly arranged.